2015
DOI: 10.1590/1678-4162-8454
|View full text |Cite
|
Sign up to set email alerts
|

Impact or push-off lameness presentation is not altered by the type of track surface where horses are trotted

Abstract: This study aimed to evaluate the influence of the track surface on which horses are examined, regarding the phase of lameness presentation. Ten horses with lameness in at least one limb were evaluated with wireless inertial sensors on three track surfaces (concrete, loose sand and grass). Six crossover track sequences were established. The variables vector sum, maximum and minimum height of the head and pelvis, variation coefficient of the maximum and minimum height of the head and pelvis were analyzed using A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…An asphalt surface was used for most of the trot-up examinations of the horses in both Singapore and Hong Kong; however, a number of horses were sampled whilst trotting in-hand on a rubber-over-concrete surface for the HKJC cohort, and the effect of the trot-up surface on the results was not tested in this investigation. Previous work by Azevedo et al (2015) showed that the impact or push-off lameness presentation for both front and hindlimbs are not altered by the type of track surface that horses trot on [43]. As all surfaces used for this study were considered firm, there was no anticipated effect of the surface type on the measures taken from the gait assessment between the STC and HKJC cohorts and within the HKJC cohort.…”
Section: Discussionmentioning
confidence: 76%
“…An asphalt surface was used for most of the trot-up examinations of the horses in both Singapore and Hong Kong; however, a number of horses were sampled whilst trotting in-hand on a rubber-over-concrete surface for the HKJC cohort, and the effect of the trot-up surface on the results was not tested in this investigation. Previous work by Azevedo et al (2015) showed that the impact or push-off lameness presentation for both front and hindlimbs are not altered by the type of track surface that horses trot on [43]. As all surfaces used for this study were considered firm, there was no anticipated effect of the surface type on the measures taken from the gait assessment between the STC and HKJC cohorts and within the HKJC cohort.…”
Section: Discussionmentioning
confidence: 76%